Cytokine Levels in Panic Disorder: Evidence for a Dose-Response Relationship. Issue 2 (February 2017) - Belem da Silva, Cristiano Tschiedel; Costa, Marianna de Abreu; Bortoluzzi, Andressa; Pfaffenseller, Bianca; Vedana, Flávia; Kapczinski, Flávio; Manfro, Gisele Gus
ABSTRACT: Objective: Several studies have investigated possible biological correlates of mental disorders. Although some studies have consistently reported elevated levels of serum inflammatory markers in depression, very few have evaluated cytokine levels in patients with lifetime panic disorder (PD). Methods: Seventy-eight adults (75% women) from an anxiety disorders outpatient unit were categorized according to their PD status: current or in remission. Serum levels of interleukin (IL)-6, tumor necrosis factor α, and IL-10 were evaluated using flow cytometry with enhanced sensitivity flex sets. Data on clinical comorbidity, lipid profile, fasting blood glucose, C-reactive protein, and PD severity were also obtained. Results: Significantly higher mean levels of serum IL-6 (0.83 vs 0.60 pg/mL [95% confidence interval CIfor the log-transformed mean difference, −0.41 to −0.57], p = .008) but not of tumor necrosis factor-α (0.18 vs 0.14 pg/mL [95% CI, −1.12 to 0.11]; p = 0.53) or IL-10 (0.21 vs 0.26 [95% CI, −0.20 to 0.44]; p = 0.16), were associated with current PD compared to remitted PD. Higher Panic Disorder Severity Scale (standardized β = 0.36; p = .013), body mass index (standardized β = 0.53, p < .001) and fasting blood glucose 5.6 mmol/L or greater (standardized β = 0.23, p = .038) were significantly associated with higher levels of IL-6 in the multivariate linear regression model. Conclusions: Our findings support a proinflammatory state in patients with current PD that is independent of possible confounders. Although there are important implications of these findings, replication is required. Abstract : Supplemental digital content is available in the text.